Relationship Between Mathematical Anxiety Levels and Mathematics Learning Outcomes - Zefania Desi; Anisa Zahro Salsabila Pramista; Muh.Suni Robi Salman Alfarisi; Fitriyah Amaliyah (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
This study aims to determine whether there is a relationship between the level of mathematical anxiety and student learning outcomes. This study uses a quantitative approach using a correlation test . The population consists of fifth-grade students at SD 2 Panjang, Kudus Regency, with a total of 11 students selected using a saturated sampling technique . Data collection techniques are carried out through questionnaires and tests. Data analysis is carried out by applying three statistical methods, namely the normality test, linearity test, and correlation test. The results of the correlation test show that H 0 is accepted with a correlation coefficient of -0.475, so it can be concluded that there is moderate negative relationship between the level of mathematical anxiety and students' mathematics learning outcomes. The higher the level of mathematical anxiety felt by students, the lower the mathematics learning outcomes they obtain. Conversely, the lower the level of mathematical anxiety, the higher the students' mathematics learning outcomes.